Serum YKL-40 and Cardiovascular Diseases - Aşkın, Lütfü; Tanrıverdi, Okan (Cerrahpaşa Medical Journal, 2024)
Abstract: YKL-40 is a glycoprotein synthesized by several cell types, including macrophages, neutrophils, and endothelial cells. It plays a role in several biological processes, such as tissue remodeling, inflammation, and cell proliferation. Research findings have shown that levels of YKL-40 tend to be higher in individuals diagnosed with cardiovascular diseases (CVDs), including atherosclerosis. Elevated concentrations of YKL-40 have been associated with detrimental CV outcomes. In general, while the precise function of YKL-40 in CVDs is still under investigation, it is evident that this glycoprotein has significant potential as a biomarker for CVDs. Furthermore, CVD treatment has the potential to specifically target the protein YKL-40. Cite this article as: Aşkın L, Tanrıverdi O. Serum YKL-40 and cardiovascular diseases. Cerrahpaşa Med J. 2024;48(2):185-190.